Pengaruh Kemampuan Penalaran Formal Terhadap Hasil Belajar Kimia Siswa SMA Negeri 1 Jayapura - Cartika Candra Ledoh (Departement of Mathematics Education, 2024)
The main objective of this research is to determine the formal reasoning abilities of students in class The approach used in this research is a descriptive and associative approach. The data collection technique used is the Test of Logical Thinking (TOLT). From the data analysis, it was found that the reasoning ability of class 2023/2024 academic year with person product moment correlation obtained a value of rx1y = 0.909 and KP 82.6%. There is an influence between formal reasoning abilities on learning outcomes in the main subject matter of chemistry XI MIA 1 SMA N 1 Jayapura for the 2023/2024 academic year with line equations linear regression Y = 69.79 + 0.311X.